The inverse scattering problem for acoustic waves in unbounded inhomogeneous medium - Kędzierawski, A.W. (Нелинейные граничные задачи, 2000)
The inverse scattering problem of determining the complex absorption coefficient of an unbounded, penetrable and inhomogeneous medium from a knowledge of the far-field patterns of the scattered fields corresponding to many incident time-harmonic plane acoustic waves is solved by using the orthogonal projection method of Colton-Monk.